Living color - Jenkins, Steve, 1952- (Houghton Mifflin, 2007)
"Red, blue, yellow, green, orange, purple, pink -- animals can be amazingly colorful. Why are they found in so many hues? How do their brilliant feathers, scales, shells, and skin help them survive? Find out ... how animals use color to warn predators, signal friends, attract a mate, or hide from their enemies"--Front dust jacket flap.